2004
DOI: 10.1089/0892779041271508
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nephroureterectomy for Adult Incontinence Caused by Functioning Ectopic Pelvic Kidney Draining into Vagina

Abstract: A 29-year-old woman had been continent of the majority of her urine for her entire life but had constant, uncontrollable dribbling. A contrast CT scan showed a solitary functioning left kidney and a dysplastic right pelvic kidney with a tortuous dilated ureter running close to the vaginal vault. The kidney was removed whole at transperitoneal laparoscopy, rendering the patient continent. This is the first such case reported in an adult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Laparoscopic surgical approaches have previously been described and developed for the treatment of duplex kidney systems and ectopic ureters 1 2 4. We demonstrated that robotic surgery can be used safely and effectively in the hands of experienced robotic surgeons for management of such cases.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Laparoscopic surgical approaches have previously been described and developed for the treatment of duplex kidney systems and ectopic ureters 1 2 4. We demonstrated that robotic surgery can be used safely and effectively in the hands of experienced robotic surgeons for management of such cases.…”
Section: Discussionmentioning
confidence: 86%
“…This arrangement has previously been identified as an explanation for continuous urinary incontinence 2 4. In addition, due to its relative rarity, it is a diagnosis which is frequently overlooked by many clinicians 1…”
Section: Discussionmentioning
confidence: 92%
“…The patient resumed normal daily activities within 2 weeks of surgery. Challacombe and colleagues 14 reported a case of a 29-year-old incontinent woman who underwent laparoscopic nephroureterectomy for a functioning dysplastic ectopic pelvic kidney with a tortuous dilated ureter draining into the vagina. The patient was rendered continent following the procedure.…”
Section: Discussionmentioning
confidence: 99%